The Application of Knowledge Management in Realising a Learning Organization in Training Institutions - Manshur Riadli; Tina Rahmawati (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study aims to analyse the implementation of knowledge management and its role in fostering learning organisations within training institutions. A mixed-methods approach with a concurrent embedded design was employed, in which qualitative data served as the primary source and quantitative data as supporting evidence. Data were collected from institutional leaders, knowledge management administrators, and staff through interviews, observations, document analysis, and questionnaires. The findings indicate that knowledge management is implemented through systematic stages, including the identification, acquisition, storage, utilisation, and evaluation of knowledge. The effectiveness of its implementation is influenced by key factors such as human resources, organisational culture, and information systems. In addition, the presence of structured learning forums, integrated learning systems, and the use of digital technologies reflect the characteristics of a learning organisation within the institutions. Quantitative analysis further reveals that knowledge management has a positive and significant effect on the development of a learning organisation. This study contributes to the field of educational technology by demonstrating how knowledge management practices can support organisational learning through technology-enabled systems. The findings provide practical implications for training institutions in designing more effective knowledge management strategies to enhance organisational performance and sustainability.